Women Emancipation and Community Development in Katine Soroti District Eastern Uganda. - Kiiza, Onesmas (Kabale University, 2025)
This study investigated the role of women's emancipation in promoting community development in Katine, Soroti District, Eastern Uganda. The research focused on three objectives: (i) examining the impact of women's participation in politics on housing status, (ii) identifying challenges faced by women's emancipation movements in fostering development, and (iii) exploring strategies to enhance women's participation in community development. Findings aim to provide insights into empowering women as key contributors to sustainable community growth.